Keeping animal spirits asleep : the case of Chile - Sáez, Sebastián (Policy research working paper, 2005)
"Chilean legislation is quite conservative, especially compared with international practice. However, its application has not been free of criticism, and it proved necessary to seek mechanisms that combine limitations set forth in the GATT/WTO regulations and others self-imposed by Chilean law. Legislation on antidumping measures was introduced in Chile in 1992. The Distortions Commission has recommended and the President has adopted such measures on just six occasions, of which two correspond to extensions of existing measures. Legislation on safeguard measures was introduced in 1999. In the 1999-2002 period, seven safeguard measures were adopted. The traditional agricultural sector was the main user of the measures, and no measure was in place for more than 12 months. The context in which the Commission was created in 1981 and the type of measures adopted by this entity support the idea that the objective of the Commission was to alleviate the political pressures generated by the difficult economic situation rather than to correct problems originated by the price distortions of goods. In the second half of the 1980s, the Commission supported the liberalization process that started in 1985. Adopting safeguard legislation in 1999 helped to gain approval of further tariff reductions from 11 percent to 6 percent. During the decade of the 1990s and until the present day, the philosophy of minimal use to further liberalization has been maintained. The legislation has undergone modifications to adjust the instruments used to support the economic opening and international commitments. "--World Bank web site